Optimizing the Intracellular Delivery of Therapeutic Anti-inflammatory TNF-α siRNA to Activated Macrophages Using Lipidoid-Polymer Hybrid Nanoparticles - Lokras, Abhijeet; Thakur, Aneesh; Wadhwa, Abishek; Thanki, Kaushik; Franzyk, Henrik; Foged, Camilla (Frontiers in Bioengineering and Biotechnology, 2021)
RNA interference (RNAi) has an unprecedented potential as a therapeutic strategy for reversibly silencing the expression of any gene. Therapeutic delivery of the RNAi mediator, i.e., small interfering RNA (siRNA), can be used to address diseases characterized by gene overexpression, for example inflammatory conditions like chronic obstructive pulmonary disease (COPD). Macrophages play a key role in COPD pathogenesis and are recruited to the airways and lung parenchyma, where they release proinflammatory cytokines, e.g., tumor necrosis factor-alpha (TNF-α). Hence, targeting TNF-α with siRNA is a promising therapeutic approach for COPD management. However, a safe and effective delivery system is required for delivery of TNF-α siRNA into the cytosol of hard-to-transfect macrophages. The purpose of this study was to optimize the intracellular delivery of TNF-α siRNA to the lipopolysaccharide-activated murine macrophage cell line RAW 264.7 using lipidoid-polymer hybrid nanoparticles (LPNs) composed of the lipid-like transfection agent lipidoid L5 and the biodegradable polymer poly(D,L-lactide-co-glycolide). Applying a quality by design approach, the influence of critical formulation variables, i.e. the L5 content and the L5:siRNA ratio (w/w), on critical quality attributes (CQAs) were investigated systematically using risk assessment and design of experiments, followed by delineation of the optimal operating space (OOS). The CQAs were identified based on the quality target product profile and included size, polydispersity index, zeta potential, encapsulation efficiency and loading for achieving efficient and safe TNF-α gene silencing in activated RAW 264.7 cells. Formulations inducing efficient gene silencing and low cytotoxicity were identified, and the optimal formulations displayed L5 contents of 15 and 20% (w/w), respectively, and an L5:siRNA weight ratio of 15:1. All tested formulations within the OOS mediated efficient and sequence-specific TNF-α gene silencing in RAW 264.7 cells at TNF-α-siRNA concentrations, which were significantly lower than the concentrations required of non-encapsulated TNF-α-siRNA, highlighting the benefit of the delivery system. The results also demonstrate that increasing the loading of siRNA into the delivery system does not necessarily imply enhanced gene silencing. This opens new avenues for further exploitation of LPNs as a robust platform technology for delivering TNF-α siRNA to macrophages, e.g., in the management of COPD.